Global entangled inequalities: conceptual debates and evidence from Latin America - Jelin, Elizabeth; Campos Motta, Renata; Costa, Sérgio (Taylor and Francis, 2017)
"Cover" -- "Endoresment" -- "Half Title" -- "Series Page" -- "Title Page" -- "Copyright Page" -- "Table of Contents" -- "List of Figure" -- "List of Tables" -- "Contributing Authors" -- "Introduction" -- "Studying dynamics of global entangled inequalities " -- "The structure of the book" -- "Notes" -- "References" -- "Part 1 Structuring inequalities" -- "Chapter 1 Inequality: Toward a world-historical perspective" -- "1 Why a world-historical unit of analysis?" -- "2âGlobal patterns of social mobility" -- "3âThe transformation of global inequality" -- "4âConclusion" -- "Notes" -- "References" -- "Chapter 2 Transregional articulations of law and race in Latin America: A legal genealogy of inequality" -- "Introduction" -- "1âAddressing race as transregional inequality: the central roleÂ of law" -- "Racial inequality regimes in Latin America" -- "Conclusion" -- "Notes" -- "References" -- "Chapter 3 The urban space and the (re)production of social inequalities: Decoupling income distribution and patterns of urbanization in Latin American cities" -- "Introduction: city and inequality in Latin America" -- "Neoliberalism, globalization, and inequality inÂ LatinÂ American cities" -- "Urban fragmentation and inequality in Latin American cities" -- "Decoupling income distribution and patterns of urbanization in the Metropolitan Region of Buenos Aires" -- "Epilogue: inequalities, urban space, and public policies" -- "Notes" -- "References" -- "Chapter 4 Researching inequalities from a socio-ecological perspective" -- "Introduction" -- "Conceptualizing socio-ecological dimensions of inequalities: Research fields and theoretical perspectives" -- "Political ecology " -- "Environmental justice " -- "Interdependencies of nature and social inequalitiesâ a conceptual proposal grounded in critical theory
Keywords: Aufsatzsammlung; Soziale Schichtung; Verteilungsgerechtigkeit; Soziale Ungleichheit; Lateinamerika